Development of a Web-Based Interactive E-Learning Platform for a Vocational High School - Qothrun Nada Alfath; Ruslan Rizki Hidayat; Zainul Hakim; Sri Rahayu (bit-Tech, 2025)
Digital transformation is essential in modern education, particularly at SMK Bina Am Ma’mur, where traditional learning methods, such as printed materials and the WhatsApp application, are still primarily used. These conventional methods limit flexibility, interactivity, and student engagement, which are crucial for effective learning. To address these challenges, this study develops an interactive web-based e-learning platform designed to enhance the learning experience at SMK Bina Am Ma’mur. The research employs a Research & Development (R&D) methodology, guided by the ADDIE model, which includes five phases: Analyze, Design, Development, Implementation, and Evaluation. Data were collected through literature reviews, observations, interviews with teachers, expert validation, and student feedback, followed by descriptive analysis to interpret the results. The validation process revealed that the developed platform is highly feasible for educational use. Media experts rated it 95% suitable, while subject matter experts provided a 91% rating. Additionally, the platform received an 89% approval rating from students, indicating its effectiveness in improving material comprehension and engagement. These findings suggest that the interactive e-learning platform is a highly effective tool for enhancing the learning process at SMK Bina Am Ma’mur, making learning more flexible, accessible, and engaging. This innovative platform has the potential to overcome the limitations of traditional media, fostering greater student motivation, interactivity, and overall learning outcomes, particularly in vocational education.